Is There Still a Role for the Second Chamber? An Italian Perspective - La Placa, Ferdinando (Brill, 2025)
The paper wants to gauge the current relevance of the bicameral systems, focusing, primarily, on the rationales that traditionally brought to the adoption of the bicameral model and, then, specifically, on the Italian case. It will so first try to retrace the debate and the historical reasons that justified the emergence of bicameralism, showing how its purposes (representation, ponderation and safeguard) evolved and adapted in the contemporary constitutional systems. Therefore, referring to the Italian system, it will seek to analyse the constituent discussion and the evolution of the Italian bicameral model. Finally, considering its current state and the recent proposal of the ruling right-wing coalition to introduce the direct election of the Prime Minister, the paper will attempt to evaluate if the Italian bicameral system is still consistent with its rationales, if it should be reformed or if it should be abandoned in favour of a unicameral model.